2018
DOI: 10.12705/676.17
|View full text |Cite
|
Sign up to set email alerts
|

Typification and nomenclatural notes on Psidium cattleyanum (Myrtaceae)

Abstract: Psidium cattleyanum is a species of Myrtaceae native to the eastern coast of Brazil, widely naturalized in tropical and subtropical regions of the world due to its economic potential to be commercially exploited. Despite its importance, the name has not previously been typified. A lectotype is designated, and the correct spelling of the epithet is shown to be "cattleyanum" not "cattleianum" as was originally published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Os compostos fenólicos têm grande diversidade química, desempenhando um papel muito importante na saúde humana, pelo seu potencial nutricional, antioxidante, antimicrobiano e antinflamatório (Tuler et al, 2018). Estes compostos são provenientes prioritariamente do metabolismo secundário das plantas, que estão diretamente ligados ao metabolismo primário e sintetizados através da via do acetato e chiquimato e pela metabolização dos fenilpropanoides em plantas (Figura 3).…”
Section: Compostos Fenólicos Do Araçáunclassified
“…Os compostos fenólicos têm grande diversidade química, desempenhando um papel muito importante na saúde humana, pelo seu potencial nutricional, antioxidante, antimicrobiano e antinflamatório (Tuler et al, 2018). Estes compostos são provenientes prioritariamente do metabolismo secundário das plantas, que estão diretamente ligados ao metabolismo primário e sintetizados através da via do acetato e chiquimato e pela metabolização dos fenilpropanoides em plantas (Figura 3).…”
Section: Compostos Fenólicos Do Araçáunclassified
“…Psidium is the third largest genus of the angiosperm family Myrtaceae in Brazil, comprising about 65 species (Tuler et al 2020). Recent phylogenetic studies have demonstrated the genus to be monophyletic (Costa 2009;Vasconcelos et al 2017;Tuler et al 2019), while recent taxonomic studies have improved species circumscription (e.g., Landrum & Sobral 2006;Landrum & Funch 2008;Soares-Silva & Proença 2011;Landrum & Proença 2015;Landrum 2017;Tuler et al 2016Tuler et al , 2018Tuler et al , 2019Tuler et al , 2020. However, many nomenclatural issues among species of the genus remain unclear.…”
Section: Introductionmentioning
confidence: 99%